2011
DOI: 10.1007/s11661-011-0823-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow and Defect Formation in the Three-Dimensional Dendritic Structure of Nickel-Based Single Crystals

Abstract: Fluid flow within the dendritic structure at the solid-liquid interface in nickel-based superalloys has been studied in two directionally solidified alloy systems. Millimeter-scale, three-dimensional (3D) datasets of dendritic structure have been collected by serial sectioning, and the reconstructed mushy zones have been used as domains for fluid-flow modeling. Flow permeability and the influence of dendritic structure on flow patterns have been investigated. Permeability analyses indicate that the cross flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…Figure 9 puts our results in contrast with the equations presented by Madison et al 18 and Poirier et al 17 For all three cases, the curves are shown for k 1 growth in the dendrite tip region and restricted growth below and (at least under these conditions) is wrongly predicted by the empirical relation of Poirier by up to a factor of 100 for high fraction liquid values. For prediction of fluid-flow phenomena in the upper part of the mushy zone (e.g., the initiation of freckles during electro-slag remelting (ESR)), 2 this can have significant consequences.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Figure 9 puts our results in contrast with the equations presented by Madison et al 18 and Poirier et al 17 For all three cases, the curves are shown for k 1 growth in the dendrite tip region and restricted growth below and (at least under these conditions) is wrongly predicted by the empirical relation of Poirier by up to a factor of 100 for high fraction liquid values. For prediction of fluid-flow phenomena in the upper part of the mushy zone (e.g., the initiation of freckles during electro-slag remelting (ESR)), 2 this can have significant consequences.…”
Section: Discussioncontrasting
confidence: 85%
“…This can be easily explained by the fact that in our phase-field simulations, the primary dendrite distance k 1 was modified ''artificially'' without changing the local thermal parameters (temperature gradient and cooling rate). To the contrary, the formulae by Poirier 17 and Madison 18 assume the change of k 1 to be attributed to a change of the local thermal condition (i.e., they assume that the dendrites have selected their primary distance according to the local conditions). Thus, no similarity should be expected with respect to the k 1 -dependency of the cross-permeability because the main effect, which is the change of k 2 due to an altered local solidification time, has not been included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…(8)). This seems to be in conflict with measurements of the freckle composition in alloy 718 implying that freckles are fed by a melt originating from a region in the mushy zone with a fraction liquid of about 0.4-0.6 [30,43]. However, it can be assumed that, even if freckles are initiated at considerably higher liquid fractions, they will erode the dendritic network, locally increase permeability, and thus penetrate downward deeper into the mushy zone.…”
Section: Discussionmentioning
confidence: 78%
“…8. In a first step, the dynamic permeability in isothermal direction was calculated using the Blake-Kozeny-relation as a function of the fraction liquid [43]:…”
Section: Application To Industrial Esr Castingmentioning
confidence: 99%
“…Spowart and Mullens later developed an automated approach to serial sectioning by combining a 6-axis robot arm, an inverted optical microscope, an ultrasonic bath, and a polishing wheel with interchangeable diamond abrasive films. This system was shown to successfully serial-section a variety of material systems [16][17][18][19][20][21][22]. UES, Inc. later purchased the rights to license this tool, commercialized the product, and have deployed units worldwide [23].…”
Section: Introductionmentioning
confidence: 99%